2019
DOI: 10.1002/elps.201900236
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis of spherical soft particles in electrolyte solutions: A review

Abstract: Theories on the electrophoresis of spherical soft particles suspended in an electrolyte solution are thoroughly reviewed. The review predominantly covers studies on the electrophoresis in dilute and concentrated suspensions as well as bounded media, carried out mainly during the past two decades. Moreover, studies on the electrostatics of soft particles are also surveyed. Finally, the research gaps and prospects of the electrophoresis of soft particles are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 128 publications
0
25
0
Order By: Relevance
“…Electric fields have been extensively employed for separation and manipulation of nanoparticles. Suspended nanoparticles in a solution subjected to an electric field experience electrokinetic phenomena such as electrophoresis and dielectrophoresis (DEP). , Electrophoresis is the migration of charged particles under the influence of a uniform electric field, wherein the field is constant in magnitude and direction between the two oppositely charged electrodes. , In a uniform electric field, charged particles are drawn to the oppositely charged electrode, whereas uncharged particles are not influenced by the field (Figure A). ,, Different charged particles subjected to a uniform electric field experience different electrophoretic forces depending on the strength of the applied field, surrounding medium condition (viscosity, pH, and ionic strength), and electrophoretic mobility of particles. , DEP is the migration of electrically polarizable (dielectric) particles within a nonuniform electric field . Particles, whether charged or neutral, in a nonuniform electric field become polarized and therefore move as a result of experiencing unbalanced electrostatic forces (Figure B).…”
Section: Label-free Microfluidic Methods For Exosome Isolationmentioning
confidence: 99%
“…Electric fields have been extensively employed for separation and manipulation of nanoparticles. Suspended nanoparticles in a solution subjected to an electric field experience electrokinetic phenomena such as electrophoresis and dielectrophoresis (DEP). , Electrophoresis is the migration of charged particles under the influence of a uniform electric field, wherein the field is constant in magnitude and direction between the two oppositely charged electrodes. , In a uniform electric field, charged particles are drawn to the oppositely charged electrode, whereas uncharged particles are not influenced by the field (Figure A). ,, Different charged particles subjected to a uniform electric field experience different electrophoretic forces depending on the strength of the applied field, surrounding medium condition (viscosity, pH, and ionic strength), and electrophoretic mobility of particles. , DEP is the migration of electrically polarizable (dielectric) particles within a nonuniform electric field . Particles, whether charged or neutral, in a nonuniform electric field become polarized and therefore move as a result of experiencing unbalanced electrostatic forces (Figure B).…”
Section: Label-free Microfluidic Methods For Exosome Isolationmentioning
confidence: 99%
“…4 shows that at high electrolyte concentrations the contribution of the particle core (μ c ) vanishes and the mobility tends to a constant value corresponding to Eq. (36).…”
Section: Case (Iii) Charged Particle Core With a Charged Polymer Layermentioning
confidence: 99%
“…There are a lot of theoretical studies on the electrophoresis of hard particles [1–18] and soft particles [19–37]. Soft particles, that is, soft‐matter‐coated particles consist of the particle core covered with an ion‐penetrable surface layer of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the micro-detection and therapy of bone crack by diffusiophoresis is a good demonstration as the injured or ill human tissues often release specific chemicals [5]. Indeed, although electrophoresis is still the major workhorse for now in various practical applications utilizing electrokinetic flows [6][7][8][9], diffusiophoresis is coming from behind with a fast pace, especially in the field of drug delivery with the reasons mentioned above [10][11][12][13]. In particular, many important experimental studies were reported by Shin et al recently to broaden the potential practical applications of diffusiophoresis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%